Recent trends in water research :Hydrochemical and hydrological perspectives - Chidambaram, S. (I.K. International Pub. House, 2010)
Contributed articles presented at the National Seminar on Recent Trends in Water Research organized by Dept. of Earth Sciences, Annamalai University; articles in Indian context.